424 A SIMPLE DISSEMINATED INTRAVASCULAR COAGULATION SCORE PREDICTS OUTCOME IN TRAUMA PATIENTS. (1st January 2005) - Zein, J.; Chbeir, E.; Albrecht, R.; Castle, C.; Taylor, F. B.; Kinasewitz, G. T.
Abstract : Purpose: Overt DIC in trauma patients is uncommon but associated with increased mortality. Recently we have found that a simple evolving DIC score based on the absolute value and change in platelet count (PC) and prothrombin time (PT) predicts the clinical course and outcome in patients with severe sepsis. We sought to determine the applicability and prognostic significance of this simple evolving DIC score in patients with trauma. Methods: This retrospective observational study examined 252 adults admitted to the trauma ICU at OUHSC. Forty-five patients who died in the ER or within the first 48 hours were excluded, as were 20 additional patients with insufficient data. A simple DIC score was calculated for each patient with 1 point for each of the following: 20% decrease in PC; an increase in PT > 0.3 seconds; an absolute PC < 100 × 103; and PT > 15.0 seconds. Patients were grouped by DIC score. Data are presented as mean ± SEM. Results: Age, gender, temperature, and WBC count were similar in all groups but the incidence of penetrating injury was higher with DIC score > 2. A worsening DIC score was associated with more severe injury (higher TRISS and ISS score, creatinine, AST, bilirubin, glucose, base deficit and, lower blood pressure, GCS, hemoglobin, PaO2/FiO2 ratio, plasma HCO3 and pH level (all p < .05). Mortality rose from 5% to 70% with DIC scores increased from 0 to 4. RBC, FFP and platelet transfusions were higher in the high DIC group (p < .05). A score ≥ 2 at 72 hours has an 85% sensitivity and 79% specificity of predicting mortality in patients presenting with trauma. Conclusion: A simple DIC score > 2 is associated with increased mortality and morbidity. An evolving DIC score taking into account the absolute value and change in 2 readily available global coagulation tests, PT and PC, is easy to use and provides useful prognostic information for the trauma patient.